The Influence Of Leadership Style And Organizational Culture On Employee Performance Through Job Satisfaction At The Department Of Industry And Trade Of Deli Serdang - Renta Herawaty Dongoran; Robert Tua Siregar; Fajar Rezeki Ananda Lubis (International Journal of Economics, Business and Innovation Research, 2026)
This study aims to analyze the influence of leadership style and organizational culture on employee performance through job satisfaction at the Deli Serdang Industry and Trade Office. This study used a quantitative-associative causal method, involving 44 respondents selected through a saturated sampling technique. Data were collected through questionnaires, observations, and literature reviews, analyzed using validity, reliability, classical assumptions, and path analysis using SPSS 26. The results of this study indicate that leadership style has no significant effect on employee performance or job satisfaction, employee performance also has no significant effect on job satisfaction, and job satisfaction does not act as an intervening variable. Meanwhile, organizational culture has a positive, significant, and dominant effect on performance and job satisfaction. This confirms that in public service organizations, improving employee performance and well-being is not effectively achieved through optimizing individual leadership or psychological mechanisms alone, but rather through strengthening an institutionalized, collective, and value-oriented organizational culture as the primary foundation of sustainable public governance.